Pelatihan Media Penunjang Kegiatan P5 Bagi Siswa SMA Sunan Giri Menganti Gresik - Widiartin, Tjatursari; Saurina, Nia; Indra Prasetya, Noven; Kukuh Adisusilo, Anang; Syidada, Shofiya; Ihsan Pribadi, Teguh (Universitas Wijaya Kusuma Surabaya, 2024)
P5 stands for the Pancasila Youth Profile Strengthening Project. This project is part of the Merdeka curriculum. P5 is one of the Indonesian government's efforts to realize the values of Pancasila in the education system of the nation's next generation. P5 activities must basically be holistic, contextual, learner-focused, and exploratory. Whatever type of activity is carried out, in the end each student is required to make a report on the results of the activity in the form of videos, posters, books, and so on. Through this Community Service activity, mentoring training will be carried out for Sunan Giri Menganti Gresik High School students so that they have a variety of P5 activities and are easy to make activity reports by introducing several media that will support the making of activity reports.